Globalization and small/firearms: a public health perspective - Cukier, Wendy; Collins, Cindy; Chapdelaine, Antoine (1999)
Violence has been identified as a pandemic to which no country is immune and represents a major threat to human security and rights. The authors look at the effects of arms availability on public health as well as on individual security, human rights and economic growth. - Reproduced
Keywords: Public health; Globalization; Health services